2023
DOI: 10.3390/ijerph20021276
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Agro-Industrial Wastewater Model Compound by UV-A-Fenton Process: Batch vs. Continuous Mode

Abstract: The degradation of a model agro-industrial wastewater phenolic compound (caffeic acid, CA) by a UV-A-Fenton system was investigated in this work. Experiments were carried out in order to compare batch and continuous mode. Initially, batch experiments showed that UV-A-Fenton at pH 3.0 (pH of CA solution) achieved a higher generation of , leading to high CA degradation (>99.5%). The influence of different operational conditions, such as H2O2 and Fe2+ concentrations, were evaluated. The results fit a pseudo fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…The range of PMS and Co 2+ concentrations was consistent with those previously assayed in the treatment of agro-industrial wastewaters by other authors [45,46]. The LED lamps were selected as radiation sources due to (1) the LED efficiency, (2) the LED price and (3) the maximum emission wavelength [47,48].…”
Section: Sr-aop Optimization Through Response Surface Methodologysupporting
confidence: 73%
“…The range of PMS and Co 2+ concentrations was consistent with those previously assayed in the treatment of agro-industrial wastewaters by other authors [45,46]. The LED lamps were selected as radiation sources due to (1) the LED efficiency, (2) the LED price and (3) the maximum emission wavelength [47,48].…”
Section: Sr-aop Optimization Through Response Surface Methodologysupporting
confidence: 73%
“…Thus, the increase in iron concentration improved the H 2 O 2 decomposition into hydroxyl radicals [4]. However, excessive iron can cause the consumption of HO • radicals by Fe 2+ , which negatively affects the degradation of organic pollutants and increases the operational cost [9].…”
Section: Photo-fenton Processmentioning
confidence: 99%
“…In Figure 2d, it can be observed that the increase in H 2 O 2 concentration was responsible for an improvement in DOC efficacy removal, i.e., 60.6% of 77.6 mM, 68.9% of 97.0 mM, 75.1% of 116.4 mM, 76.3% of 135.8 mM, and 76.6% of 155.3 mM. An excessive H 2 O 2 concentration can cause scavenging reactions between H 2 O 2 and HO • , causing the generation of hydroperoxyl and superoxide anion radicals [9]. However, with the gradual addition of 116.4 mm of H 2 O 2 at 0, 15, 30, 60, and 90 min, an improvement in DOC removal from 75.1 to 80.5% was verified.…”
Section: Photo-fenton Processmentioning
confidence: 99%
“…Conventional methods are not much effective in removing and/or degrading these compounds due to the persistence related to their molecular properties and chemical structures 3 . Although these chemicals are detected in trace amounts, prolonged exposure can cause adverse effects on human health as well as aquatic life.Therefore, treating these pollutants from wastewater is obligatory before discharging them 4 .…”
Section: Introductionmentioning
confidence: 99%